Formulation and Evaluation of Fixed-Dose Combination Immediate Release Tablets of Ibuprofen and Famotidine through Quality by Design Approach (Bangladesh Pharmaceutical Journal, 2021)
Nonsteroidal anti-inflammatory drugs (NSAIDs) are frequently prescribed by the physicians for the management of pain due to their anti-inflammatory and analgesic properties. Long term use of NSAIDs causes gastrointestinal (GI) toxicity and the common GI disorders are indigestion, ulcers or bleeding. Therefore, the production of local oral tablets containing NSAIDs and gastro-protectant is inevitable. In this experiment, combination of ibuprofen 600 mg and famotidine 20 mg tablets were prepared by direct compression technique, which is unique in Bangladesh. To pursue the study Design of Experiments (DoE) approach was implemented to create fifteen trial formulations where Polyvinylpyrrolidone (PVPK30) 1%-3%, Microcrystalline Cellulose (Avicel PH-102) 1%-7% and Starch-1500 1%-13% were considered as independent variables and the responses were depicted in friability and disintegration time which were found 0.21–0.45% and 1.8–20.5 minutes respectively. Out of fifteen formulation trials (F-1 to F-15), seven formulations (F-3, F-6, F-8, F-9, F-10, F-13 and F-14) had met the acceptable criteria and one formulation (F-9) with independent variables PVP-K30 2.00%, Avicel PH-102 4.75% and Starch-1500 6.5% was selected because of its better disintegration, dissolution and friability profile. Data obtained from in-vitro dissolution tests were fitted to different kinetic models such as zero order, first order, Higuchi, Hixson-Crowell and Korsmeyer-Peppas models. Also, a compatibility study was conducted using Fourier Transform Infrared Spectroscopy (FTIR), Thermogravimetric Analysis (TGA) and X-Ray Diffraction (XRD). Furthermore, Scanning Electron Microscopy (SEM) was performed to analyze surface morphology. Finally, the selected formulation was compared to FDA regulated QC parameters and proved its superiority over conventional market products.Bangladesh Pharmaceutical Journal 24(2): 133-148, 2021